Pericardial effusion after congenital heart surgeryCentral MessagePerspective - Mio Noma, MD; Yasutaka Hirata, MD; Norimichi Hirahara, PhD; Takaaki Suzuki, MD; Hiroaki Miyata, PhD; Yuji Hiramatsu, MD; Yukihiro Yoshimura, MD; Shinichi Takamoto, MD (JTCVS Open, 2022)
Objective: Pericardial effusion after cardiac surgery remains an important cause of morbidity and mortality. We describe the risk factors of pericardial effusion after congenital heart surgery through analyzing data from a nationwide, multi-institutional registry. Methods: The Japan Congenital Cardiovascular Surgery Database, which reflects routine clinical care in Japan, was used for this retrospective cohort study. Multivariable regression analysis was done after univariable comparison of patients with pericardial effusion and no pericardial effusion. Results: The study enrolled 64,777 patients registered with the Japan Congenital Cardiovascular Surgery Database between 2008 and 2016; 909 of these had postoperative pericardial effusion (1.4%) and were analyzed along with 63,868 patients without pericardial effusion. Univariable analysis found no difference between the groups in terms of gender, early delivery, or preoperative mechanical ventilatory support. In the pericardial effusion group, cardiopulmonary bypass use was lower (58.4% vs 62.1%), whereas the cardiopulmonary bypass time (176.9 vs 139.9 minutes) and aortic crossclamp time (75.1 vs 62.2 minutes) were longer, and 30-day mortality was higher (4.1% vs 2.2%). Multivariable analysis identified trisomy 21 (odds ratio, 1.54), 22q.11 deletion (odds ratio, 2.17), first-time cardiac surgery (odds ratio, 2.01), and blood transfusion (odds ratio, 1.43) as independent risk factors of postoperative pericardial effusion. In contrast, neonates, infants, ventricular septal defect, atrial septal defect, tetralogy of Fallot repair, and arterial switch operation were correlated with a low risk of pericardial effusion development. Conclusions: The incidence of postoperative pericardial effusion in congenital cardiac surgery was 1.4%. Trisomy 21, 22q.11 deletion, first-time cardiac surgery, and blood transfusion were identified as the principal factors predicting the need for pericardial effusion drainage.